Clinical Characteristic of the HIV/AIDS Patients with Cryptosporidiosis Referring to Behavioral Diseases Consultation Center, Imam Khomeini Hospital, Tehran in 2013 - Rashid Gholami; Shirzad Gholami; Hamid Emadi-Kouchak; Alireza Abdollahi; Mona Shahriari (Iranian Journal of Pathology, 2016)
Background: Cryptosporidiumis known as an opportunist disease-causing agent in man in recent decades. It causes diarrhea and intestinal disorders in the immune deficit and immune competent individuals. This study was aimed to investigate the clinical characteristics of HIV/AIDS patients withcryptosporidiosisinfection. Methods: This cross-sectional descriptive study was performed on 53 HIV/AIDS patients referred to the Behavior Disease Consultation Center of Imam Khomeini Hospital in Tehran, Iran in 2013. First, the patients were studied clinically and the context data were recorded in a questionnaire for parasitological examination and referred to the laboratory for eosinophil count, and CD4 count per ml of blood. Results: Cryptosporidiosiswas observed in 4 (7.6%) of the total 53 HIV/AIDS patients. The highest prevalence of infection was observed in the age range of 30-39 yr.Itwas observed in different sexes as 5.7% of male and 1.9% of female, but statistically was insignificant (P=0.163).75% of patients had no intestinal symptom, 11.4% with acute diarrhea and 3.8% with chronic diarrhea. Cryptosporidiosis cases were observed in 5.7% of patients without intestinal symptom. Conclusion: Practitioners in the clinicalexamination for the detectionof the opportunistic intestinal protozoan infection should use clinical and paraclinical characteristics of the HIV/AIDS patients for the diagnostic of Cryptosporidium and other opportunistic parasitic diseases.